2016
DOI: 10.1111/jocn.13154
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to falls, weight‐loss and pressure ulcers – more insight in risk assessment among nursing home residents

Abstract: A more comprehensive view is needed and prevention can not only be based on total scores. Mobility is an important factor for falls and pressure ulcers, both as a risk factor and a protective factor. This involves a challenge for care--to keep the inmates physical active and at the same time prevent falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 33 publications
(36 reference statements)
4
45
0
6
Order By: Relevance
“…There is a well-known relationship between poor nutritional status and pressure ulcers [10,45]. The lowest prevalence of falls was found among those with risk for malnutrition and pressure ulcers probably explained by these individuals being less mobile and more often bed ridden compared to the rest of the population, as was also shown in an earlier study [46].…”
Section: Discussionmentioning
confidence: 64%
“…There is a well-known relationship between poor nutritional status and pressure ulcers [10,45]. The lowest prevalence of falls was found among those with risk for malnutrition and pressure ulcers probably explained by these individuals being less mobile and more often bed ridden compared to the rest of the population, as was also shown in an earlier study [46].…”
Section: Discussionmentioning
confidence: 64%
“…The mean age at inclusion was 85 years (±6.9) and the median age was 85, with a range between 65 and 101 years. In some earlier studies on the SHADES cohort 429 subjects were included [129][130][131][132][133][134], but one subject was found to be 64 years old and excluded from later studies.…”
Section: Resultsmentioning
confidence: 99%
“…Papers III-IV focus on anaemia, associations between falls and drugs, and cognitive impairment respectively. In addition to the papers on which this thesis is based, there are several other articles published on various aspects of the SHADES population [129][130][131][132][133][134][135][136][137][138][139].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to risk management, institutions must contemplate an environment that fosters the well being and dignity of older adults, recognizing the complexity of promoting their safety when institutionalized (29) . A study in Sweden revealed that merely 4% of the institutionalized older adults had not suffered falls, malnutrition or pressure ulcers (30) . This is to be expected, considering the dependency and frailty of most older adults residing in long-term care institutions.…”
Section: Discussionmentioning
confidence: 99%